Navigating Cross-Border Healthcare under Structural Vulnerability: The Role of Cultural Health Capital - Kellilynn M. Frias; Deidre Popovich; Mikaela Trussell (Journal of Service Research, 2026)
This research examines how Hispanic women living in the US–Mexico borderlands coordinate household healthcare across two national service systems through the lens of cultural health capital (CHC). Drawing on multimethod ethnography using in-depth interviews, participant observation, and online diaries, we show how informants build and deploy navigational, social, familial, and linguistic capital to manage structural vulnerability in cross-border care. Findings demonstrate that women purposefully cultivate and allocate these forms of capital across three phases of healthcare shopping: pre-consumption, during shopping, and post-purchase. We identify consumer practices through which capital helps families navigate structural barriers, while also showing that such strategies emerge under conditions of constraint and do not eliminate exposure to risk. The study advances consumer vulnerability research by integrating structural vulnerability with CHC to theorize phase-specific capital orchestration and by specifying how intersecting vulnerability factors shape both exposure and response. We also translate these mechanisms into service design implications for providers, payers, and policymakers. In doing so, this research highlights the need for safer, more coordinated, and more culturally responsive care pathways that recognize the informal labor and cross-cultural expertise sustaining healthcare access in marginalized communities.